2011
DOI: 10.1557/opl.2011.1151
|View full text |Cite
|
Sign up to set email alerts
|

CdSxTe1-x Alloying in CdS/CdTe Solar Cells

Abstract: A CdSxTe1-x layer forms by interdiffusion of CdS and CdTe during the fabrication of thinfilm CdTe photovoltaic (PV) devices. The CdSxTe1-x layer is thought to be important because it relieves strain at the CdS/CdTe interface that would otherwise exist due to the 10% lattice mismatch between these two materials. Our previous work [1] has indicated that the electrical junction is located in this interdiffused CdSxTe1-x region. Further understanding, however, is essential to predict the role of this CdSxTe1-x lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 6 publications
3
9
0
Order By: Relevance
“…For the untreated sample, there is a high Cl signal on the surface, while Cl signal becomes uniform in the HI‐treated device. Similar native oxides and chlorides have been observed on CdTe surfaces treated by CdCl 2 . Raman spectroscopy analysis revealed a significant increase in the intensity of stretching modes of Te–Te vibrations after the HI treatment (Figure d), indicating the formation of a Te‐rich back surface as reported in the literature .…”
Section: Resultssupporting
confidence: 85%
“…For the untreated sample, there is a high Cl signal on the surface, while Cl signal becomes uniform in the HI‐treated device. Similar native oxides and chlorides have been observed on CdTe surfaces treated by CdCl 2 . Raman spectroscopy analysis revealed a significant increase in the intensity of stretching modes of Te–Te vibrations after the HI treatment (Figure d), indicating the formation of a Te‐rich back surface as reported in the literature .…”
Section: Resultssupporting
confidence: 85%
“…The previous speculation of phase segregation during the annealed alloy films is apparently confirmed, because the S concentration is much higher in area "a", which is found to represent CdS 0.956 Te 0.044 . Given the relative high error limit of EDX measurements, ±1% [18], this result should be considered as consistent with the data reported by McCandless [14]. We also recorded fluorescence spectra for other "bright" zones; these spectra confirmed the high S concentrations.…”
Section: Constituents Of the Filmssupporting
confidence: 91%
“…To fabricate a CdS nanodipole solar cell, heavily n‐type ITO1 was first deposited on glass substrate, followed by sputtering of the CdS x Te 1−x mixed layer. ITO1 is n‐type doped, and the Te‐rich CdS x Te 1−x after CdCl 2 treatment is usually weakly p‐type . Thus, a junction field, E junction1 , exists at ITO1/CdS x Te 1−x interface, with direction from ITO1 toward CdSTe layer as shown in Figure (a).…”
Section: Resultsmentioning
confidence: 99%
“…Several experimental results are consistent with Equation (1) for CdS x Te 1´x [16,19,39], but according to our knowledge, there are no experimental or theoretical results for CdS 1´y Te y . For CdS x Te 1´x alloy, Duenow et al [16] found that the bandgap decreases below the CdTe bandgap value of E g(CdTe) = 1.5 eV, to as low as 1.41 eV at x -0.3, before increasing at higher x values. Ohata et al [39] have shown that the bandgap of CdS x Te 1´x alloy decreases with addition of S in the Te-rich region for values of x up to 0.25.…”
Section: T (Nm) Y = [Te]/([te] + [S]) 10´2 ([In]/[cd])% In the Filmsupporting
confidence: 77%
“…Nakayama et al [17], who studied sulfur diffusion within CdTe, found that the positions of CdTe peaks are slightly shifted and observed satellites. Murali et al [19] showed that the variation of lattice spacing and lattice parameters with composition is linear and obeys Vegard's law [16]. Table 1 besides the thickness of the films and the percentage ratio of indium to cadmium in the solution.…”
Section: Structure Composition and Morphologymentioning
confidence: 93%